THE INTRODUCTION AS A PART OF COMPOSITIONAL STRUCTURE OF THE LAUDATORY SPEECH - Natalya I. Palamar (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article provides an in-depth overview of the peculiarities of the Introduction as a part of the compositional structure of the laudatory speech based on the analysis of German and Ukrainian laudatory speeches. The Introduction along with the Main Body and Conclusion form a universal static structural body of any speech. Each part has its own specific features which are taken into account at the preparation stage. Particular attention is paid in the article to the biggest in amount structural part, namely the Main Body, i.e. the layout which contains arguments supporting a particular standpoint. The introduction (the opening part) and the closing part form the so-called framing of the speech. Laudation is viewed in the article as a specific speech type realized in public, a direct (face-to-face) type of communication unrestricted by any temporal and spatial boundaries, which is characterised by the absence of spontaneity and is monologic by its nature. As the name of this speech type suggests, its subject matter finds itself in praise of a particular person. The peculiarity of the Introduction to the laudatory speech lies in the idiosyncratic nature of the introduction to the topic (the setting of the scene). Delivered at solemn ceremonies on the occasion of anniversary celebrations or prize awards, this speech type starts its realisation with the Address to the audience and the laureate/ hero of the day. The Address, in general, expresses respect for the audience and is viewed as a key attention-grabber. The main introductory topics of the studied laudatory speeches are as follows: the demonstration of the relevance of the topic and its significance for the audience, the expression of the feeling of honour to be delivering the speech, the appeal to wisdom quotes, sayings and aphorisms, the reference to rules observed while delivering speeches or the speaker’s task, the use of jokes or recollections of some humorous situations, a short account of the occasion on which the congratulations are offered, and the congratulations to the addressee on a particular occasion or date. Thus, a wide range of openings to the laudatory speech singled out in terms of the conducted analysis is diverse and depends on the nature of the topic, the person delivering the speech, i.e. the laudator, peculiarities of the occasion, etc. Nevertheless, the task of the Introduction is static (invariable) and finds itself in stimulating the audience’s interest, attracting attention to the subject-matter and the transition to the main body, even though the carried out analysis showed some qualitative differences in the range of topics covered in introductions to laudatory speeches in two languages. The latter might be accounted for by the diversity in subject matter of the laudatory speeches selected for the current analysis, the specificity of the national character and ways of thinking peculiar to the studied cultures.